(untitled) (Comparatismi, 2022)
The writing of the self is a field of election in the trauma’s processing. The COVID-19 pandemic has led to a global situation of collective trauma being processed in personal and community forms. The «Revista de la Universidad de México» promoted a Diario de la pandemia with articles published regularly to keep the feeling of daily pages testifying the pandemic waves. French-Hungarian writer Nina Yargekov took part with her article Sondage: un lapin sort grand gagnant. The personal story of pandemic trauma is declined through the use of playful way, humour, pastiche and parody, giving rise to an original mixture of reality and fiction. Yargekov, through autofictional writing, attempts to reconstruct what she calls psychisme fracturé. Her testimony, balanced between socio-political analysis and intimate reflection, shows the therapeutic aspect of writing: resilience.